Pembiasaan Sikap Tasamuh Santri Melalui Pembelajaran Rebana Kolosal - Bakhruddin, A.; Risasongko, Anjar Anggita (Jurnal Penelitian, 2022)
This research is motivated by the low habituation of the tasamuh attitude possessed by students at the Tasywiqul Furqon Islamic Boarding School in everyday life. Besides that, the learning method used in learning does not activate students, so students are easily bored and don’t even focus when receiving lessons. This study aims to determine the effectiveness of learning the colossal tambourine in order to increase the habituation of the santri’s tasamuh attitude and whether there are significant changes to the learning of the santri colossal tambourine. This research is a pre-experimental study with a one group pretest posttest research design. Data were obtained using pretest and posttest worksheets. The result show that there is a significant result (2-tailed) 0.000<0.05 which means that Ho is rejected and H1 is accepted. This shows that there is an effectiveness and a significant change in the learning of colossal tambourine in order to increase the habituation of the student’s tasamuh attitude. The average acquisition score of N after learning is 85.98 and before learning is only 67.61